Discord between presence of follicular conjunctivitis and Chlamydia trachomatis infection in a single Torres Strait Island community: a cross‐sectional survey. (3rd January 2022) - Lynch, Kathleen D.; Brian, Garry; Ahwang, Tomasina; Newie, Tomi; Newie, Victoria; Perrett, Christine; Wharton, Ghislaine; Brown, Anthony; Tozer, Sarah; Kaldor, John M.; Whop, Lisa J.; Andrews, Ross M.; et al.
Abstract: Objective : Recent surveys identified trachomatous inflammation – follicular (TF) at endemic levels in the Torres Strait Islands; however, local health staff do not report trachomatous trichiasis (TT) in adults. We undertook a cross‐sectional survey involving eye examination and microbiological testing to better understand this disconnect. Methods : We examined 169 of 207 (82%) residents and collected ocular swabs for polymerase chain reaction (PCR) testing for Chlamydia trachomatis . Other viral PCR tests and bacterial culture were also performed. Results : TF prevalence in children aged 5–9 years was 23% (7/30). No ocular C. trachomatis was identified by PCR. For the 72 participants (43%) with follicles, bacterial culture was positive for 11 (15%) individuals. No individual had trachomatous trichiasis. Conclusions : Follicular conjunctivitis consistent with TF was prevalent but ocular C. trachomatis and cicatricial trachoma were absent. Non‐chlamydial infections or environmental causes of follicular conjunctivitis may be causing TF in this community. Implications for public health : In similar settings, reliance on simplified clinical assessment alone may lead to an overestimation of the public health problem posed by trachoma. Consideration should be given to incorporating C. trachomatis PCR, and in certain settings, a detailed clinical exam could be performed by an experienced ophthalmologist during prevalence surveys.